Strategi Peningkatan Kualitas Pelayanan Satuan Pendidikan untuk Mewujudkan Inklusi yang Memuliakan dengan Sirami Tamanmu - Eko Mulyadi; Suyatno; Muhammad Sayuti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The education report card of SMAN 1 Pengasih climate inclusivity in 2023 with a score of 59.19, in 2024 with a score of 69.97, it will increase, in 2025 with a score of 67, it will decrease. Disability services in 2023 will have a score of 71.3, in 2024 with a score of 70.68, it will decrease, in 2025 with a score of 61, the last three years have decreased. Meanwhile, attitudes towards disabilities in 2023 will score 58.62, in 2024 the score will be 70.95, and in 2025 the score will be 69.08, which will decrease. In 2025, schools will be entrusted with 6 inclusion students, but the education unit is not optimal in providing services: accompanying teachers, infrastructure facilities and learning services. The objectives of good practice: 1) Fulfilling the needs of the number of inclusion companions, 2) Improving infrastructure facilities, especially access to inclusion, 3) Inclusion learning services. In order to optimize serving and glorifying, the principal held the SIRAMI TAMANMU program, an acronym for the Smapta Inclusive Education Unit Serving and Glorifying. Steps in fulfilling the climate of inclusivity, disability services and attitudes towards disabilities are optimal, the number of accompanying teachers through previous education and training is held from 2 people to 3 people and scanning to other teachers, the original infrastructure facilities already have 1 to 2 wheelchairs, the addition of inclusion bathrooms, 1 langsam derivative, 2 inclusion drop points, 1 inclusion parking point and learning services are spread out with regular classes. The partnership with SLB PGRI Minggir is related to Inclusion. Inclusion students have achieved both academically and sports up to the DIY level.